2021
DOI: 10.1111/jop.13267
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐1 promotes cancer progression via inhibiting ferroptosis in head and neck squamous cell carcinoma

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is an aggressive disease worldwide. Much progress has been made in exploring mechanisms and improving the therapy of HNSCC, but only a few studies have focused on the role of ferroptosis on HNSCC progression. The current study aimed to reveal the underlining mechanisms that caveolin-1 (CAV1)-ROS (reactive oxygen species)-ferroptosis axis affect the process of HNSCC and discover novo therapeutic targets or strategies. Methods:The role of CAV1 in ferropto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Ferroptosis has been reported to modulate the TME to inhibit tumor progression and improve prognosis (19,20). Our study first developed a novel risk-scoring model based on 5 ferroptosis-related prognostic genes from SCLC data from the cBioPortal dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferroptosis has been reported to modulate the TME to inhibit tumor progression and improve prognosis (19,20). Our study first developed a novel risk-scoring model based on 5 ferroptosis-related prognostic genes from SCLC data from the cBioPortal dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that activation of ferroptosis can overcome tumor development and reduce the sensitivity of the tumor to chemotherapy ( 8 ). Ferroptosis has been reported to modulate the TME to inhibit tumor progression and improve prognosis ( 19 , 20 ). Our study first developed a novel risk-scoring model based on 5 ferroptosis-related prognostic genes from SCLC data from the cBioPortal dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, sequence-based studies have shown that ferroptosis-related gene signature plays an important role in the development and treatment of HNSCC [ 18 20 ]. CAV1, which could inhibit ferroptosis, leads to cancer progression in HSNCC [ 21 ]. Li et al reveal that IL-6 induces ferroptosis resistance by protecting tumor cells from ROS and promoting HNSCC progression [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by dysbalance in the regulation of intracellular iron metabolism and membrane lipid peroxidation ( Ursini and Maiorino, 2020 ). The function of ferroptosis in several types of cancer has been reported previously, including breast cancer ( Li H. et al, 2022 ), hepatocellular carcinoma ( Chen et al, 2022 ), gastric cancer ( Zhang et al, 2021 ), head neck squamous cell carcinoma ( Lu et al, 2021 ), lung cancer ( Li and Liu, 2022 ), renal cell carcinoma ( Du et al, 2021 ), ovarian cancer ( Li H.-W. et al, 2022 ), and pancreatic cancer ( Liu et al, 2021 ). Mou et al (2022 ) has found that for LGG the SAT1 activation is closely related to ferroptosis upon ROS induction.…”
Section: Introductionmentioning
confidence: 69%